Features of the Organization of Paid Medical Services in the Russian Federation and in the Federal Republic of Germany - Ansell G. LAMMERT; Svetlana V. LEZHENINA; Nadezhda V. SHUVALOVA; Jeanne S. VASILIEVA; Nikolay A. EFREMOV; Olga A. FILIPPOVA; Tatiana V. MUZHZHAVLEVA; Marina P. EFREMOVA; Alina A. FEDOTOVA (Communications of International Proceedings, 2021)
The purpose of the article is to analyze the actual and not yet resolved problem of the commercialization of Russian healthcare, which is being investigated by the authors in the context of international experience, assessments of expert organizations (WHO, ILO, World Bank). The methodological research toolkit combines a systematic analysis of a complex of information sources. Research prospects are associated with the need and relevance of the search for reasonable boundaries of state participation in health care, as well as tools for consolidating the efforts of the public and private sectors in the field of public health, including through the implementation of public-private partnership projects. Summarizing the data obtained in the literature review, it can be noted that the healthcare management system in market conditions should provide a flexible combination of the system of guaranteed free medical services and paid medical services. For this, it is necessary to create a competitive environment in healthcare, expand the organizational and legal forms of medical activity, including state, municipal joint-stock medical institutions, partnerships, individual private medical enterprises and private practitioners engaged in self-employment. The management system should also increase the motivation of health workers to achieve high end results of work and ensure the required level of efficiency in the functioning of health services.
Keywords: Health care of the Russian Federation and the Federal Republic of Germany; paid medical services; health care financing.